2014
DOI: 10.4049/jimmunol.1302821
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 Shapes Macrophage Polarization by GM-CSF and M-CSF: Identification of CCL2/CCR2-Dependent Gene Expression Profile

Abstract: The CCL2 chemokine mediates monocyte egress from bone marrow and recruitment into inflamed tissues through interaction with the CCR2 chemokine receptor, and its expression is upregulated by proinflammatory cytokines. Analysis of the gene expression profile in GM-CSF– and M-CSF–polarized macrophages revealed that a high CCL2 expression characterizes macrophages generated under the influence of M-CSF, whereas CCR2 is expressed only by GM-CSF–polarized macrophages. Analysis of the factors responsible for this dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
284
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 409 publications
(330 citation statements)
references
References 77 publications
25
284
2
3
Order By: Relevance
“…More recently, it was also found that CSF-1-differentiated macrophages obtained from human PBMC express and produce CCL2, while GM-CSF-differentiated macrophages express CCL2R. CD14 + TAM isolated from ascitic fluid of different types of cancer express CCL2 at an even higher extent that CSF-1-differentiated macrophages [102]. Taken together, the above-described results support further a protumoral activity of CSF-1R signaling.…”
Section: Pro-tumoral Activity Of Csf-1r Signaling In Tamsupporting
confidence: 72%
“…More recently, it was also found that CSF-1-differentiated macrophages obtained from human PBMC express and produce CCL2, while GM-CSF-differentiated macrophages express CCL2R. CD14 + TAM isolated from ascitic fluid of different types of cancer express CCL2 at an even higher extent that CSF-1-differentiated macrophages [102]. Taken together, the above-described results support further a protumoral activity of CSF-1R signaling.…”
Section: Pro-tumoral Activity Of Csf-1r Signaling In Tamsupporting
confidence: 72%
“…1C). As expected, the four Mf populations expressed the lineage-specific marker PU.1 (32) (Fig. 1E), whereas M14 and M16 exhibited higher levels of MAFB and HO-1 (molecules associated with the M-Mf phenotype) (32,33) than did GM14 and GM16 (Fig.…”
Section: Phenotypic and Functional Features Of Gm-and M-csf-derived Mmentioning
confidence: 73%
“…Previous reports have described differences in iron and folate metabolism between antitumoral/bactericidal and tumor-promoting macrophages (8) and between GM-MØ and M-MØ (9). A clear dichotomy exists in L-arginine metabolism between murine macrophages exposed to either LPS/IFN-g (high producers of NO via inducible NO synthase) or IL-4 (producers of ornithine and urea via Arginase-1).…”
mentioning
confidence: 99%